2021
DOI: 10.1007/s10493-020-00586-z
|View full text |Cite
|
Sign up to set email alerts
|

How land-use intensity affects sexual and parthenogenetic oribatid mites in temperate forests and grasslands in Germany

Abstract: Intensive land use has been shown to alter the composition and functioning of soil communities. Due to their low dispersal ability, oribatid mites are particularly vulnerable to land-use intensification and species which are not adjusted to management-related disturbances become less abundant. We investigated how different land-use parameters in forests and grasslands affect oribatid mite diversity and abundance, with a focus on: (1) species-level impacts, by classifying species as increasing (‘winners’) or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Literature evidence showed that post-disturbance communities are mainly constituted by few high-adaptable species, such as Tectocepheus sp. (mites) and some species belonging to Entomobrydae (springtails) ( Maraun et al, 2003 ), or by species with disturbance-adapted strategies, such as parthenogenetic reproduction ( Wehner et al, 2021a ). On the contrary, other studies found that richness of springtails increased in disturbed plot ( Urbanovičová, Kováč & Miklisová, 2010 ; Urbanovičová, Miklisová & Kováč, 2014 ), and others found divergent responses in abundance and species richness ( Čuchta, Miklisová & Kováč, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence showed that post-disturbance communities are mainly constituted by few high-adaptable species, such as Tectocepheus sp. (mites) and some species belonging to Entomobrydae (springtails) ( Maraun et al, 2003 ), or by species with disturbance-adapted strategies, such as parthenogenetic reproduction ( Wehner et al, 2021a ). On the contrary, other studies found that richness of springtails increased in disturbed plot ( Urbanovičová, Kováč & Miklisová, 2010 ; Urbanovičová, Miklisová & Kováč, 2014 ), and others found divergent responses in abundance and species richness ( Čuchta, Miklisová & Kováč, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some oribatid mite species show an equal 1:1 sex ratio, whereas for most species female-biased (72%-69%) sex ratios are observed (Domes et al 2007). Interestingly, a large number of asexual species exist in the Oribatida that reproduce in the absence of sex over a substantial amount of time (Brandt et al 2021; Wehner et al 2021; Öztoprak et al 2023).…”
Section: Introductionmentioning
confidence: 99%